Specific types of bladder cancer - Bertz, Simone; Hartmann, Arndt; Knuechel-Clarke, R.; Gaisa, N. T. (Pathologe, 2016)
Bladder cancer shows rare variants and special subtypes with diverse prognostic importance and therefore may necessitate different therapeutic approaches. For pathologists it is important to histologically diagnose and specify such variants. Nested variants of urothelial carcinoma with inconspicuous, well-formed tumor cell nests present with an aggressive course. The plasmacytoid variant, which morphologically resembles plasma cells is associated with a shorter survival time and a high frequency of peritoneal metastasis. Micropapillary urothelial carcinoma with small papillary tumor cell islands within artificial tissue retraction spaces and frequent lymphovascular invasion also has a poor prognosis. Other important rare differential variants listed in the World Health Organization (WHO) classification are microcystic, lymphoepithelioma-like, sarcomatoid, giant cell and undifferentiated urothelial carcinomas. Additionally, there are three special types of bladder cancer: squamous cell carcinoma, adenocarcinoma and small cell neuroendocrine carcinoma of the bladder. These tumors are characterized by pure squamous cell or glandular differentiation and are sometimes less responsive to adjuvant (chemo)therapy. Small cell carcinoma of the bladder mimics the neuroendocrine features of its pulmonary counterpart, shows an aggressive course but is sensitive to (neo-)adjuvant chemotherapy. The morphology and histology of the most important variants and special types are discussed in this review.
EVALuna2:6786